An Efficient Multicomponent Reaction for the Synthesis of New Benzofuran-pyrazole Hybrids: In Situ Approach and Antioxidant Activity (Journal of Scientific Research, 2026)
A one-pot, base-assisted method was used to synthesise tetrahydrobenzofuran-pyrazole derivatives (4a-4j) in acetonitrile under reflux utilising 4-(1H-pyrazol-1-yl)benzaldehyde, 5,5-dimethylcyclohexane-1,3-dione, and phenacyl bromides. After rigorously optimising catalysts, solvents, and reaction conditions, Et3N with pyridine in acetonitrile gave high yield in 6 h. After substrate scope analysis, 4-methoxy, 3,4-dimethoxy, and 3,4,5-trimethoxy derivatives failed to produce stable products due to steric and electronic effects while 4-thiomethyl phenacyl bromide decomposed and lacrimated due to its instability. Synthesised compounds' antioxidant potential was evaluated using the DPPH assay. The strongest radical-scavenging activity was found in 4-nitro (4a, IC50= 12.90 µM) and 4-ethyl (4i, IC50= 14.50 µM) derivatives, equivalent to ascorbic acid (IC50 = 12.10 µM. However, halogen-substituted derivatives showed moderate to weak action, with 4-fluoro (4d, IC50 = 56.01 µM) being the least effective.